The reclassification of the genus Ceratocaryum Nees (Restionaceae) and describing the variation of the species C. argenteum Nees ex Kumth - Hawley, Greer (Department of Biological Sciences, 2017)
Estuarine systems are characterised by relatively high levels of salinity due to their connection with the sea. Zandvlei has been victim too much manipulation for the sake of flood prevention, recreation and water level regulation. One of the largest impacts on the system is the rubble weir placed at the mouth of the outlet channel that was built to maintain water levels in the drier summer months. There is evidence that the salinity in the estuary is declining, as the weir inhibits sufficient tidal ingress. Resultant consequences include encouraging the growth of alien invasive weeds, the decline of indigenous aquatic fauna and flora, and a shift in ecosystem functioning. Plans to increase the circulation of seawater have already been proved to be necessary, but the process needs to be monitored. Diatoms are used regularly in Europe to monitor water quality in terms of eutrophication and pollution. This study attempts to describe the change in diatom composition after the mouth has been manually opened, in terms of the influencing factors, namely salinity and temperature. The species response was found to be a shift in species dominance rather than a species turnover. Key indicator species were distinguished by the response to salinity. Diatoms can also be informative ofthe stability of the Vlei and therefore act as a valuable tool for monitoring purposes.